Estructura de capital y rentabilidad de las microempresas del sector de construcción de la ciudad de Loja. - Enríquez Díaz, Lenin Raúl (2023)
In the context in which companies operate today, financial management occupies a fundamental place in decision-making regarding their capital structure. This is a topic on which there is great controversy among scholars and researchers; Determine the optimal combination of own and external resources that generate greater business value. The research aims to analyze the capital structure and profitability of microenterprises in the construction sector of the city of Loja, considering a quantitative and qualitative approach, through the application of deductive, inductive and analytical methods, in which 37 construction microenterprises existing in the Loja canton were analyzed, the information was compiled from the portal of the Superintendence of Companies, Securities and Insurance during the period 2020-2022. Through the application of a multiple linear regression model, the relationship between the ROE that was influenced by the ratio of Debt to Equity (DEUP) was determined. While the ROA did not have a significant effect due to the independent variables of the debt ratios. Finally, strategies were proposed with the purpose of strengthening and promoting a more effective management of debt levels and the achievement of business objectives. Giving as conclusions that the findings encourage the micro enterprise sector of construction to carry out an analysis of the capital structure in order to reduce and forecast relevant models that influence decision making, and that allows an appropriate use of the resources obtained.